UPAYA MENUJU DEMOKRASI DI MYANMAR TAHUN 1990 - Satyadinata, Kadek Wema (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
Abstract The purpose of this paper is to describe the efforts towards a democratic system in Myanmar in 1990. At election in 1990 pro-democracy party, the National League for Democracy Party (NLD) led by Aung San Suu Kyi won 82 percent of the vote, but the results of this election is not recognized that the ruling military regime. NLD Party's victory in the 1990 elections was a clear victory of the opposition threaten the existence of the ruling military junta government for this. This gave rise to fears of a military junta government stronghold that then makes General Maung unilaterally not recognize the results of elections and imprisoned a large number of members of the NLD party. Problems that occur in the Myanmar government seized the attention of the regional and international community because of the actions of government are oppressive junta demonstrators who support democracy. The method used in this paper is the method of literature, where the source comes from some of the literature used either a book, a journal as a reference.   Keywords: Aung San Suu Kyi, Democracy, Military Junta Government